2015
DOI: 10.4317/medoral.20384
|View full text |Cite
|
Sign up to set email alerts
|

Deep dry needling of trigger points located in the lateral pterygoid muscle: Efficacy and safety of treatment for management of myofascial pain and temporomandibular dysfunction

Abstract: BackgroundTo determine whether deep dry needling (DDN) of trigger points (TPs) in the lateral pterygoid muscle (LPM) would significantly reduce pain and improve function, compared with methocarbamol/paracetamol medication.Material and MethodsForty-eight patients with chronic myofascial pain located in the LPM were selected and randomly assigned to one of two groups (DDN test group, n=24; drug-treated control group, n=24). The test group received three applications of needling of the LPM once per week for three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
55
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(59 citation statements)
references
References 20 publications
0
55
0
3
Order By: Relevance
“…A recent systematic review showed that there is a strong evidence for dry needling to have a positive effect on pain intensity [20]. Previously studies were done on masseter and lateral pterygoid dry needling and the results were very encouraging [21,22]. In our patient, we have given two sessions of dry needling treatment over masseter, lateral pterygoid, temporalis and sternocleidomastoid.…”
Section: First Visit Second Visit Final Visitmentioning
confidence: 84%
“…A recent systematic review showed that there is a strong evidence for dry needling to have a positive effect on pain intensity [20]. Previously studies were done on masseter and lateral pterygoid dry needling and the results were very encouraging [21,22]. In our patient, we have given two sessions of dry needling treatment over masseter, lateral pterygoid, temporalis and sternocleidomastoid.…”
Section: First Visit Second Visit Final Visitmentioning
confidence: 84%
“…The application of the MEP® technique is similar to that of dry needling (DN), since both use acupuncture needles. This technique is considered safe according to the study of Gonzalez-Perez et al 6 , meta-analysis and review of Liu et al 3 , or the review by Dunning et al 22 . Therefore, it is not surprising that 56.79% (159) of the participants had no complications and that only one case (0.36%) of significant complication was reported (Needle rupture, which must be removed by surgery) and none severe 21,[23][24][25] .…”
Section: Discussionmentioning
confidence: 99%
“…Although experimental research is the scientific objective, the use of surveys can provide information on the satisfaction of patients or those who apply a technique 5,6 .…”
Section: Introductionmentioning
confidence: 99%
“…Gonzalez-Pérez et al (9) carried out a study with 48 patients with myofascial pain in the lateral pterygoid muscle. Their results showed that DN promoted local pain reduction and MMMA gain (maximum opening, lateralization, and protrusion) in patients presenting these symptoms.…”
Section: Discussionmentioning
confidence: 99%